FENOMENA MORFOTEKTONIK PADA CITRA STRM DI WILAYAH TELUK KENDARI - Yasin, Andi Makawaru; Sukiyah, Emi; Sulaksana, nana; Isnaniawardhani, Vijaya (Bulletin of Scientific Contribution, 2016)
Kendari bay has a strategic position in Southeast Sulawesi. In this region there is a city of Kendari, the capital of the province. The unique shape is a product of the collision of tectonic plates, occupies the southeast arm of Sulawesi. There might be a strong tectonic control in the region. The up lift process continues sustainable, evidence was also recorded in the landscape. The phenomenon morphotectonic show unique patterns that are easily recognizable on remote sensing data. The data used in this study is derived from SRTM imagery. Besides lineament associated with geological structure, the DEM can also be obtained from that image. Sun-shading technique used to clarify the appearance of lineament associated with geological structure. The lineament data plotted into a rosette diagram to determine the general trend. The lineament density data obtained by calculating the ratio of the total length of lineament in each grid of 5x5 sq km. The results showed that the morphotectonic phenomenon easily recognizable in the SRTM imagery. Sun-shading techniques can clarify lineament patterns associated with the presence of fault. Zone of lineament density increase indicates an irregular pattern and generally at the level of more than 400 meters above sea level, located in the northern and southern approached Wolasi Mountains. At an elevation of less than 400 meters above sea level, low lineament density between 0 to 8 km /sq km. This phenomenon indicates that the area has undergone a process of denudation. Lineament pattern trending NE-SW reflect the release of the compression process LAWANOPO shear fault trending NW-SE. Keywords: Morphotectonic, SRTM image, lineament, GIS, Kendari Bay Teluk kendari memilki nilai strategis di Provinsi Sulawesi Tenggara. Di wilayah ini terdapat Kota kendari yang merupakan ibu kota provinsi. Bentuknya yang unik merupakan produk tumbukan lempeng tektonik, berada di lengan tenggara Sulawesi. Tidak salah jika ada kontrol tektonik yang cukup kuat di wilayah ini. Proses pengangkatan secara berkesinambungan terus berlangsung, bukti-buktinya juga terekam pada bentang alam di wilayah ini. Fenomena morfotektonik menunjukkan pola-pola yang unik sehingga mudah dikenali pada data penginderaan jauh. Data yang dipergunakan dalam penelitian ini berasal dari citra SRTM.  Di samping kelurusan yang berasosiasi dengan struktur geologi, dari citra tersebut juga diperoleh DEM. Teknik sun-shading digunakan untuk memperjelas kenampakan kelurusan-kelurusan yang berasosiasi dengan struktur geologi. Data hasil interpretasi kelurusan diplot ke dalam diagram rose untuk mengetahui arah umum. Data kerapatan kelurusan diperoleh dengan cara menghitung perbandingan total panjang kelurusan dalam setiap grid yang berukuran 5x5 km2. Hasil penelitian menunjukkan bahwa fenomena morfotektonik mudah dikenal pada citra SRTM. Teknik sun-shading dapat memperjelas pola-pola kelurusan yang berasosiasi dengan keberadaan sesar. Zona peningkatan densitas kelurusan menunjukkan pola yang tidak teratur dan secara umum berada pada level > 400 mdpl, terdapat di bagian utara dan selatan mendekati Pegunungan Wolasi. Pada elevasi < 400 mdpl, densitas kelurusan rendah antara 0 sampai 8 km/km2. Fenomena ini menunjukkan bahwa daerah tersebut telah mengalami proses denudasi. Pola kelurusan berarah NE-SW mencerminkan realese dari proses compression sesar geser LAWANOPO berarah NW-SE.   Kata Kunci : Morfotektonik, citra SRTM, kelurusan, SIG, Teluk Kendari